Lehrfilm Facharztweiterbildung: Hemithyreoidektomie mit Neuromonitoring des N. laryngeus recurrens - Brunner, Maximilian; Bleichroth, Hannah; Linke, Katja; Krautz, Christian; Grützmann, Robert; Kersting, Stephan; Weber, Georg (Zentralblatt für Chirurgie, 2019)
INTRODUCTION: The mean prevalence of thyroid nodules in adults is about 20% and increases with age. Most of the thyroid nodules are benign, and are rarely malignant. However, malignancy can often only be conclusively determined after resection. Therefore, it is essential that the surgical technique should be free of complications. Despite all published minimally invasive techniques, the open procedure via a Kocher incision is still standard and commonly used in a teaching setting. This standardised technique is presented step-by-step in the video. INDICATION: Sonographic and MIBI-scintigraphic possibly malignant solitary node in the right thyroid lobe. PROCEDURE: Hemithyreoidectomy with neuromonitoring of recurrent laryngeal nerve. CONCLUSION: Hemithyroidectomy is an adequate primary therapy for a solitary possibly malignant thyroid nodule. Intraoperative neuromonitoring to identify and protect the recurrent laryngeal nerve, visualisation and protection of the parathyroid glands without compromising blood circulation and careful hemostasis are the main pillars of low risk surgery of the thyroid.
CRIS-Team Scopus Importer:2019-12-24